Stroke Among Patients With Dizziness, Vertigo, and Imbalance in the Emergency Department: A Population-Based Study - Kerber, Kevin A. (2006)
BACKGROUND AND PURPOSE: Dizziness, vertigo, and imbalance are common presenting symptoms in the emergency department. Stroke is a leading concern even when these symptoms occur in isolation. The objective of the present study was to determine the “real-world” proportion of stroke among patients presenting to the emergency department with these dizziness symptoms (DS). METHODS: From a population-based study, patients >44 years of age presenting with DS to the emergency department, or directly admitted to the hospital, were identified. Demographics, the frequency of new cerebrovascular events, and the frequency of isolated DS (ie DS with no other stroke screening term or accompanying neurologic signs or symptoms) were assessed. Multivariable logistic regression was used to evaluate the association of age, gender, ethnicity, and isolated DS with stroke/transient ischemic attack (TIA). The association of the presenting symptoms with stroke/TIA was also assessed. RESULTS: Stroke/TIA was diagnosed in 3.2% (53 of 1666) of all patients with DS. Only 0.7% (9 of 1297) of those with isolated DS had a stroke/TIA. Patients with stroke/TIA were slightly older than those without stroke/TIA (69.3±11.7 vs 65.3±12.9, P=0.02). Male gender was associated with stroke/TIA, whereas isolated DS was negatively associated with stroke/TIA. Patients with imbalance (dizziness as referent) were more likely to have stroke/TIA. CONCLUSIONS: The proportion of cerebrovascular events in patients presenting with dizziness, vertigo, or imbalance is very low. Isolated dizziness, vertigo, or imbalance strongly predicts a noncerebrovascular cause. The symptom of imbalance is a predictor of stroke/TIA.